2021
DOI: 10.9734/arja/2021/v14i430144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sex Effects on Serum Biochemical and Genetic Parameters of Japanese Quails

Abstract: The study evaluated effect of Sex on serum biochemical parameters and Correlation with body weight of Japanese quails. A total of 400 birds (200 birds per sex) were reared in a Completely Randomized Design under standard management practices for 7 weeks with feed and water given ad libitum. Sex were considered treatments. Weekly body weight (BW) was measured. The three authors have declared that, “principle of laboratory animal care” (NIH publication 85 - 23 revised 1985) were followed as well as the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…There was evidence of significant sex-related differences in ALT and AST estimates, demonstrating that females had higher values of AST and ALT than males, which may be explained by the physiological changes in metabolism in female birds due to maturation and attaining egg laying [ 45 ]. Similar findings were reported by Udoh et al [ 46 ]; however, Scholtz et al [ 47 ] reported significant differences in ALT and AST with males exhibiting lower estimates than females.…”
Section: Discussionsupporting
confidence: 88%
“…There was evidence of significant sex-related differences in ALT and AST estimates, demonstrating that females had higher values of AST and ALT than males, which may be explained by the physiological changes in metabolism in female birds due to maturation and attaining egg laying [ 45 ]. Similar findings were reported by Udoh et al [ 46 ]; however, Scholtz et al [ 47 ] reported significant differences in ALT and AST with males exhibiting lower estimates than females.…”
Section: Discussionsupporting
confidence: 88%